Augmented reality for high-throughput phenotyping - Wu, Shanshan (Kansas State University, 2019)
Smart glasses, like smart phones, have separate operating systems, and can execute many different kinds of software and games. Smart glasses can be used to add a schedule, map navigation, interact with friends, take photos and videos, and make video calls with friends through voice control. They can support wireless network access through a mobile communication network. Bluetooth is a radio technology that supports short-range communication between of the devices. It can exchange information between devices including mobile phones, wireless headsets, laptops, etc. Bluetooth technology can effectively simplify the communication between mobile devices. This thesis focuses on smart glasses applications for high-throughput phenotyping which requires a data monitor, data synchronization, Bluetooth service, and voice control between devices. On the Android side, the application, which is extended, is called Field Book. The new software called Field Book AR, includes a data monitor module and a Bluetooth server module to achieve data exchange with smart glasses. On the smart glasses side, the application is called DataReceiver. It receives voice commands from users and controls the actions of Field Book AR. Also, when Field Book detects data changing, it accepts new data and shows changes to the users.
Keywords: Augmented reality; Android app; Phonetyping; Smart glasses; Bluetooth; Voice control